Differential diagnosis for physical therapists : screening for referral - Goodman, Catherine Cavallaro; Snyder, Teresa E. Kelly (Saunders Elsevier, 2007)
Written by a leading expert in the field, this comprehensive reference text enables users to properly screen for medical disease to make an informed diagnosis. The goal of this proven text is to teach the Physical Therapist how to determine if the patient has a true neuromuscular or musculoskeletal problem and to determine the specific dysfunction or impairment. Now with a new title that reflects a better understanding of the screening process as the first step in making a diagnosis, this text provides students, physical therapy clinicians and physical therapist assistants with a step-by-step approach to client evaluation, which follows the standards of competency established by the American Physical Therapy Association (APTA) related to conducting a screening examination.A systems-based approach to differential screening and diagnosis make it easy for Physical Therapists to find information and understand it in light of other systems issues.CD-ROM with screening tools provides Physical Therapists with forms and checklists they can use in the clinical setting.Case studies provide real-world examples.New chapter on how physical assessment provides baseline-screening information to better explain the progression of the screening process.Includes new information on musculoskeletal problems.A separate chapter on pain introduces the concept of pain as a screening tool.An entire section is devoted to systematic origins of pain to demonstrate how regional pain should be approached in screening for particular disorders.Introductory information on the newer medical screening concepts sets the stage for how screening is presented in the rest of the book.
Keywords: Diagnosis, Differential; konziliární vyšetření a konzultace; Referral and Consultation; diagnostika; diferenciální diagnóza; rehabilitační a fyzikální medicína; rehabilitační lékařství; Physical Therapy Modalities; techniky fyzikální terapie; Physical and Rehabilitation Medicine